Odpowiedzi

2010-03-19T15:56:16+01:00
Tga=5
sina-cosa/sina+cosa=?
tga=sina/cosa
sina=tga*cosa
sina-cosa/sina+cosa=(tga*cosa- cosa)/(tga*cosa+cosa)=
cosa(tga-1)/cosa(tga+1)=(5-1)/(5+1)=2/3
1 5 1
2010-03-19T16:06:03+01:00
Tgα=5
sinα/cosα=5
sinα=5cosα
5cos2(kwadrat)α+cos2α=1 -z jednynki trygonometrycznej
6cos2α=1
cosα=^1/6(pierwiatek z jednej szostej)
cosα=^6/6(pierw z szesc dzielone szesc)

sin2α+(^6/6)do kwaratu=1
sin2α+1/6=1
sinα=^5/6pierwiatek z piec szostych

sinα-cosα /sinα+ cosα=^5/6-^6/6 / ^5/6+^6/6=
(^5 -^6)/6:(^5+^6)/6=^5-^6/^5+^6 * ^5-^6/^5-^6=
=(^5-^6)2(kwadrat)/5-6 =5-2^3+6=-5-2^3-6=-2^6 -11- wynik.

^-oznacza pierwiastek